Perspesi pekerja terhadap organisasi sebagai pembelajaran : satu kajian kes di Asean Bintulu Fertilizer Sendirian Berhad, Bintulu, Sarawak - Janet, Johnny (Universiti Malaysia Sarawak, (UNIMAS), 1999)
This study aims to determine the perception of the workers in a private sector, ABF Sendirian Berhad in Bintulu, Sarawak of the attainment of the organization as a learning organization. The specific objectives are to determine workers' perception of the level of support provided by the organization, consistent evaluation, feedback, information sharing and training for learning purpose. The study also compares workers' demographic factors: age, educational level, gender, marital status, working experience and training. Thirty four workers in al1 1evel in the organization were selected randomly. Data was gathered through observation and questionnaire. The data was analyzed by using SPSS-Win. The study showed that: (i) majority of the respondents (68%) perceived the organization (ABF Sdn.Bhd) attained a high level as a learning organization; (ii) there are no significant difference among workers 'perception on the organization level of attainment as a learning organization based on demographic factors excluding the marital status (t= 1.012;p<O.05), working experience factors (r=O.540;p<O.O1), learning supports(r=O.922;p<O.O1), consistence evaluation (r-O.824;p<O.O1), organization's feedback (r-O.863;p<O.O1), information provided (r=O.748;p<O.O1) and training facilities (r-0.485;p<O.O1). Based on the result of the study, it reveals the critical roles of the management in supporting and encouraging their workers in the leaning activities for the continuous development of the organization. Thus, this study proposes several recommendations to help and encourage the organization to be an excellent learning organization. It is recommended that ABFSB be more proactive and reactive in respond to the global change and also ABF Sdn Bhd must be sensitive for the needs of Ihe organization. ABF Sdn Bhd must also provide their workers with sufficient skills and knowledge to respond to the change. And also, strategic planning is critical for the development of their workers and the organization. For the future research, it is suggested that the researchers look into an organization, which is different in disciplines and places and also applies different research methods and makes comparison between organizations.